A SOLDIER’S BURIAL IN MOUND GROUP NO. 7 OF THE PALASA-SYRT BURIAL MOUND OF THE 4TH-5TH CC - Saidov, V A; Gmyra, L B (History, Archeology and Ethnography of the Caucasus, 2016)
The article deals with the unique grave goods of a man’s burial (mound 1559), which was a part of separate mound group No. 7 of the Palasa-Syrt burial mound of the 4th-5th centuries. The complex was robbed and among the preserved goods there is an iron combat knife in a sheath (of wood and leather), decorated with silver clinches with ornament incisions; a large iron clasp; flint steel with red-burnt end and other objects. The authors of the article have determined the functionality of the objects and proposed the reconstruction of the remaining holding elements on the surface of the combat knife sheath.